Effective authentication to prevent Sybil attacks in vehicular platoons - Junaidi, Danial Ritzuan (2023)
The potential ability to increase the capacity and safety on roads, as well as fuel economy gains has made vehicle platooning an appealing prospect. However, its use is yet to be widespread, partially due to the security concerns on it. One particular concern is the admission of fake virtual vehicles into the platoons, allowing them to wreak havoc on the platoon, which is known as a Sybil attack. In this paper, we propose a secure vehicular authentication scheme for platoon admission which is resistant to the threats of Sybil attacks. The proposed scheme offers a mutual authentication on both vehicle identity and message through a combination of a key exchange, a digital signature and an encryption scheme based on Elliptic Curve Cryptography (ECC). The scheme holds its outstanding feature to provide both perfect forward secrecy and group backward secrecy to ensure the protection of anonymity of vehicles and platoons while typical malicious attacks such as replay, and man-in-the-middle attacks can also be resisted. A formal evaluation of the security of the scheme by Canetti-Krawczyk (CK) adversary and random oracle model has been conducted to demonstrate its security functionality. Finally, the performance of the proposed scheme has been evaluated to show its efficiency.